Ophthalmic Diagnosis and Novel Management of Infantile Refsum Disease with Combination Docosahexaenoic Acid and Cholic Acid - Omar Elghawy; Alice Y. Zhang; Ryan Duong; William G. Wilson; Eugene Y. Shildkrot (Case Reports in Ophthalmological Medicine)
Infantile Refsum disease is a rare peroxisomal biogenesis disorder characterized by impaired alpha-oxidation and accumulation of phytanic acid in the tissues. Patients often present with fundus changes resembling retinitis pigmentosa, developmental delay, sensorineural hearing loss, ataxia, and hepatomegaly. Traditionally, mainstay treatment for this condition has been a phytanic acid-restricted diet, although supplementation with either docosahexaenoic acid or cholic acid has rarely been described in the literature. We present a case of infantile Refsum disease in a child with retinitis pigmentosa-like ocular findings, sensorineural hearing loss, and self-resolving hepatic disease, who developed novel findings of macular edema refractory to carbonic anhydrase inhibitors. We describe management with a phytanic acid-restricted diet and combination docosahexaenoic acid, and cholic acid therapy, which helped to limit progression of her disease.